Dispensing error rate after implementation of an automated pharmacy carousel system. - Oswald S; Caldwell R (American Journal of Health-System Pharmacy, 2007)
PURPOSE: A study was conducted to determine filling and dispensing error rates before and after the implementation of an automated pharmacy carousel system (APCS). METHODS: The study was conducted in a 613-bed acute and tertiary care university hospital. Before the implementation of the APCS, filling and dispensing rates were recorded during October through November 2004 and January 2005. Postimplementation data were collected during May through June 2006. Errors were recorded in three areas of pharmacy operations: first-dose or missing medication fill, automated dispensing cabinet fill, and interdepartmental request fill. A filling error was defined as an error caught by a pharmacist during the verification step. A dispensing error was defined as an error caught by a pharmacist observer after verification by the pharmacist. RESULTS: Before implementation of the APCS, 422 first-dose or missing medication orders were observed between October 2004 and January 2005. Independent data collected in December 2005, approximately six weeks after the introduction of the APCS, found that filling and error rates had increased. The filling rate for automated dispensing cabinets was associated with the largest decrease in errors. Filling and dispensing error rates had decreased by December 2005. In terms of interdepartmental request fill, no dispensing errors were noted in 123 clinic orders dispensed before the implementation of the APCS. One dispensing error out of 85 clinic orders was identified after implementation of the APCS. CONCLUSION: The implementation of an APCS at a university hospital decreased medication filling errors related to automated cabinets only and did not affect other filling and dispensing errors.